Unveiling Epigenetic Vulnerabilities in Triple-Negative Breast Cancer through 3D Organoid Drug Screening - Xinxin Rao; Zhibin Qiao; Yang Yang; Yun Deng; Zhen Zhang; Xiaoli Yu; Xiaomao Guo (MDPI AG, 2024)
Triple-negative breast cancer (TNBC) poses a therapeutic challenge due to its aggressive nature and lack of targeted therapies. Epigenetic modifications contribute to TNBC tumorigenesis and drug resistance, offering potential therapeutic targets. Recent advancements in three-dimensional (3D) organoid cultures, enabling precise drug screening, hold immense promise for identifying novel compounds targeting TNBC. In this study, we established two patient-derived TNBC organoids and implemented a high-throughput drug screening system using these organoids and two TNBC cell lines. Screening a library of 169 epigenetic compounds, we found that organoid-based systems offer remarkable precision in drug response assessment compared to cell-based models. The top 30 compounds showing the highest drug sensitivity in the initial screening were further assessed in a secondary screen. Four compounds, panobinostat, pacritinib, TAK-901, and JIB-04, targeting histone deacetylase, JAK/STAT, histone demethylases, and aurora kinase pathways, respectively, exhibited potent anti-tumor activity in TNBC organoids, surpassing the effect of paclitaxel. Our study highlights the potential of these novel epigenetic drugs as effective therapeutic agents for TNBC and demonstrates the valuable role of patient-derived organoids in advancing drug discovery.